Sense of Relationship Entitlement of Aging Parents Toward Their Offspring (SRE-ao)—A New Concept and Measurement Tool - Tolmacz, Rami; Lev-Ari, Lilac; Bachner-Melman, Rachel; Palgi, Yuval; Bodner, Ehud; Feldman, Darya; Chakir, Ron; Ben-David, Boaz (Frontiers in Psychology, 2022)
Our sense of entitlement influences our interactions and attitudes in a range of specific relational contexts, one of them being aging parents’ relationships with their adult children. This study aimed to examine the factor structure of the Sense of Relational Entitlement – aging parents toward their offspring (SRE-ao), an 11-item questionnaire that assesses aging people’s sense of relational entitlement towards their children, and examine the associations of its subscales with related personality and mental health constructs. 1006 participants (24.6% men), aged 65-99, with at least one child, completed the SRE-ao, Brief Symptom Inventory, Loneliness Scale and General Belongingness scale. The SRE-ao demonstrated good construct structure using confirmatory factor analysis. Both SRE-ao subscales (restricted and inflated sense of entitlement) were significantly and positively associated with anxiety, depression, somatization and sense of loneliness and negatively with sense of belonging. When all variables were entered into a regression model, age, anxiety, and low sense of belonging, but not sense of loneliness, positively predicted both restricted and inflated sense of entitlement. Somatization negatively predicted inflated sense of entitlement. The SRE-ao is a reliable and valid scale that can be used in clinical practice and research to enhance our understanding of parent-child relationships throughout the lifespan.